Identifying sufficient and necessary competencies in the effective use of artificial intelligence technologies - Ion Popa; Marian Mihai Cioc; Andreea Breazu; Cătălina Florentina Popa (Amfiteatru Economic, 2024)
Recently, there have been significant changes in the labour market and in the lives of employees, as modern society adapts increasingly easily to the implementation of artificial intelligence tools. However, technological changes have also created challenges, including a gap between available and required competencies in the use of artificial intelligence technologies. This study aims to analyse the relationships between employee competencies and effectiveness in the use of artificial intelligence tools, in order to highlight the set of essential competencies in effective interaction with artificial intelligence technology. Therefore, to achieve the purpose of the research, a questionnaire was created and completed by 209 Romanian employees between August and September 2023. For data analysis, two advanced techniques were applied: structural equation modelling (SEM) and necessary conditions analysis (NCA) using the SmartPLS v4 program. The results suggest that employee competencies are significantly associated with the effectiveness of using AI tools, and optimism and innovativeness positively mediate this relationship. The originality of the research stands out through the use of two advanced analysis methods (structural equation modelling and necessary conditions analysis), with the aim of identifying the set of sufficient and necessary skills in the use of artificial intelligence tools. These findings have significant implications for organisations, the educational system, and future research directions on the managerial implications of using artificial intelligence tools.
Keywords: D83; O15; I25; 330; artificial intelligence; competencies; formal education; non-formal education; effectiveness; education